Mercury effects in natural populations of sea anemone Actinia equina - Jordão, Rita Marisa Gomes (2012)
Mercury (Hg) is considered to be one of the most toxic metals to biota, being capable of biomagnification and bioaccumulation in food chains. High concentrations of Hg were associated with developmental and behavioral abnormalities, impairment in growth and reproduction, and reduced survival. Though this metal has been extensively studied, several knowledge gaps still exist, mainly regarding its effects in different types of organisms. Accordingly, this study aimed at assessing the effects of a short-term exposure to Hg in natural populations of the sea anemone Actinia equina. To attain this objective, four natural population of A. equina were sampled in the NW Atlantic coast with different levels of contamination for Hg. From each population, forty individuals were collected and acclimated in laboratory, under optimal conditions, for one month. Afterwards, organisms were weighed (7.09 ± 0.18 g mean ± SE), and using a flow-through system were exposed to 100 μg L-1 of Hg and to artificial sea water solely, during 96h. At the end of exposure, organisms were immediately deep-frozen (-80°C) until further analysis. The tissue of pedal disc was analyzed for bioaccumulation and biomarkers (biochemical: glutathione S-transferase–GST, catalase–CAT and lipid peroxidation–LPO and metabolic: lactate and alanine) to compare the uptake, oxidative damage and metabolic patterns among populations after being exposed to Hg. All population exhibited significant bioaccumulation of Hg and a significant change in LPO when exposed to Hg, as in lactate/alanine ratio. On the contrary, exposure to Hg caused no significant changes in the activities of GST and CAT. Furthermore, significant differences in the response patterns to Hg among the four populations were observed. With the two populations originated from sites with a higher Hg contamination showing a lower bioaccumulation of Hg and a higher oxidative damage. Also, the ratio of lactate/alanine (an index of redox state of the cell) revealed that those two populations exhibited a healthier redox state. These findings suggest that the use of several endpoints at different levels of biological organization is important for the evaluation of Hg effects in the biota.